Effect of Sauropus androgynus Leaf Extract plus Turmeric Powder Supplementation on Broiler Performance - Santoso, Urip; Fenita, Yosi; Suharyanto, Suharyanyo; Putranto, Agus Martono Hadi (BPFP Universitas Bengkulu, 2020)
A factorial design was used to evaluate the effect of Sauropus androgynus leaf extract (SALE) andturmeric powder (TP) on the performance of broilers fed a high-fat diet. Two dietary fat sources (6% beeftallow or 6% palm oil), and five mixtures of SALE plus TP (0 g SALE plus 0 g TP, 9 g SALE plus 0.5 g TP,18 g SALE plus 0.5 g TP, 9 g SALE plus 1 g TP, 18 g SALE plus 1 g TP) were studied. Experimentalresults showed that dietary fat sources, and SALE plus TP mixture had no effect on body weightgain, feed intake, and feed conversion ratio (P>0.05). No interaction was found between two factors(P>0.05). In conclusion, the addition of SALE plus TP to a high-fat diet did not improve broilerperformance.